Genetic analysis of drug resistance in Neisseria gonorrhoeae: production of increased resistance by the combination of two antibiotic resistance loci. - Maier, T W (1975)
The studies reported here demonstrate that increased resistance of Neisseria gonorrhoeae to penicillin, tetracycline, and chloramphenicol results from the combined effect of two resistance loci. As shown by experiments with deoxyribonucleic acid from transformants carrying only a single resistance locus, transformants with an incresed level of resistance to penicillin result from the combination of a penicillin-specific locus, pen, and a multiple resistance locus, mtr. Similarly, transformants with an increased level of resistance to tetracycline result from the combination of mtr and a tetracycline-specific locus, tet. Transformants with an increased level of resistance to chloramphenicol result from the combination of mtr and a chloramphenicol-specific locus, cml. Deoxyribonucleic acid dilution experiments established that only a single dose of each of the two required resistance loci is necessary to give higher-level resistance. Higher-level-resistant transformants were not obtained when a double dose of one resistance locus or a combination of loci pairs other than mtr and pen, mtr and tet, or mtr and cml was introduced into a recipient. Combinations of the mtr and tet genes resulted in increased resistance to semisynthetic tetracyclines. The presence of the mtr and pen genes resulted in increased resistance to penicillinase-stable penicillins.